Pengetahuan Gizi, Pola Asuh, serta Jarak Kehamilan terhadap Status Gizi Balita di Posyandu Lancang Kuning, Tuah Karya, Pekanbaru, Riau: Nutrition Knowledge, Caring Capacity, and Pregnancy Spacing to Toddler's Nutritional Status at Posyandu Lancang Kuning, Tuah Karya, Pekanbaru, Riau - Rizki Natia Wiji; Lisviarose Lisviarose; Rini Harianti; Meyroza Asriyanty (Universitas Airlangga, 2023)
Background: An individual's health can be described by the food and the nutrients consumed and absorbed by the body. The nutritional status of toddlers is influenced by infectious diseases, food intake, the mother's nutritional knowledge, caring capacity, and the distance between pregnancies. Objectives: This research aimed to analyze the correlation between nutrition knowledge, caring capacity, and the distance between pregnancies and the nutritional status of toddlers. Methods: The study used a cross-sectional design. The population was toddlers in the Lancang Kuning Posyandu, Tuah Karya, and Pekanbaru-Riau (subject 123 mothers of toddlers) through simple random sampling. The study was conducted from November 2019 - July 2020. Information was analyzed using the Chi-square test. Results: The results showed that most of the mothers of toddlers had high school education, had poor nutrition knowledge, and more than one-third had poor care capacity, and most of the children's nutritional status was good. The analysis showed a correlation between nutrition knowledge, caring capacity, the distance between pregnancies, and the nutritional status of toddlers (p<0.001; p=0.005; and p=0.041). Conclusions: Nutrition knowledge, caring capacity, and distance of pregnancy can optimize the toddler's nutritional status.